2016
DOI: 10.1371/journal.pone.0153552
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Contrast Agent Staining of Ligaments and Tendons for X-Ray Computed Tomography

Abstract: X-ray computed tomography has become an important tool for studying the microstructures of biological soft tissues, such as ligaments and tendons. Due to the low X-ray attenuation of such tissues, chemical contrast agents are often necessary to enhance contrast during scanning. In this article, the effects of using three different contrast agents—iodine potassium iodide solution, phosphotungstic acid and phosphomolybdic acid—are evaluated and compared. Porcine anterior cruciate ligaments, patellar tendons, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 27 publications
3
59
0
Order By: Relevance
“…Our protocol improves upon existing procedures by addressing a number of potentially problematic issues with contrast‐enhanced microCT. Numerous studies have reported PTA to be a less than ideal staining option, particularly as compared with iodine, due to a slower diffusion time through tissues, requiring a longer staining time . As a larger molecule, PTA will necessarily require longer staining protocols to permit full penetration into deeper tissue structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our protocol improves upon existing procedures by addressing a number of potentially problematic issues with contrast‐enhanced microCT. Numerous studies have reported PTA to be a less than ideal staining option, particularly as compared with iodine, due to a slower diffusion time through tissues, requiring a longer staining time . As a larger molecule, PTA will necessarily require longer staining protocols to permit full penetration into deeper tissue structures.…”
Section: Resultsmentioning
confidence: 99%
“…One recent study suggests that the high degree of tissue shrinkage may be related to a delay between specimen collection and staining, noting that large Alligator and Gallus specimens that were immediately fixed and stained following euthanasia did not show evidence of soft tissue shrinkage in the cranium . Balint et al reported generalized soft tissue shrinkage with morphology altering deformation in iodine‐stained porcine ligaments, occurring to a greater extent relative to ligaments stained with either PTA or PMA . Even more recent protocols that involve a tissue‐stabilization step prior to iodine staining still note observable tissue shrinkage, which may affect morphological analyses …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Recently, there have been substantial advances in microCT technology, both in terms of the types of scanner available, which now allow sub-micron resolution, capture of phase-contrast information and faster scan acquisition, and in the development of imaging protocols (Withers, 2007;Stock, 2008;Bravin et al, 2013;Maire and Withers, 2014;Shearer et al, 2014;Balint et al, 2016). Collectively, these advances can be exploited to image soft (non-calcified) tissues.…”
Section: Optical and Electron Microscopy In Three Dimensionsmentioning
confidence: 99%
“…Prior to µCT scanning at 17 µm isotropic voxel resolution, the entire organism of about 6 cm in length was immersed for four weeks in an ethanol solution with added phosphotungstic acid [83]. It would be of great interest to further explore the usefulness of this µCT-based approach for the 3D visualization of the pulp cavity and all soft tissues surrounding the human tooth, in particular since new protocols for the staining of specific tissues are now increasingly becoming available [84,85].…”
Section: Soft Tissue Imaging Using Micro-computed Tomographymentioning
confidence: 99%